Arterial pulse wave velocity but not augmentation index is associated with coronary artery disease extent and severity: implications for arterial transfer function applicability - Hope, Sarah A; Antonis, Paul; Adam, David; Cameron, James D; Meredith, Ian T (Journal of hypertension, 2007)
The aim of this study was to test the hypothesis that coronary artery disease extent and severity are associated with central aortic pressure waveform characteristics. Although it is thought that central aortic pressure waveform characteristics, particularly augmentation index, may influence cardiovascular disease progression and predict cardiovascular risk, little is known of the relationship between central waveform characteristics and the severity and extent of coronary artery disease. Central aortic waveforms (2F Millar pressure transducer-tipped catheters) were acquired at the time of coronary angiography for suspected native coronary artery disease in 40 patients (24 male). The severity and extent of disease were assessed independently by two observers using two previously described scoring systems (modified Gensini's stenosis and Sullivan's extent scores). Relationships between disease scores, aortic waveform characteristics, aorto-radial pulse wave velocity and subject demographic features were assessed by regression techniques. Both extent and severity scores were associated with increasing age and male sex (P < 0.001), but no other risk factors. Both scores were independently associated with aorto-radial pulse wave velocity (P < 0.001), which entered a multiple regression model prior to age and sex. This association was not dependent upon blood pressure. Neither score was associated with central aortic augmentation index, by either simple or multiple linear regression techniques including heart rate, subject demographic features and cardiovascular risk factors. Aorto-radial pulse wave velocity, but not central aortic augmentation index, is associated with both the extent and severity of coronary artery disease. This has potentially important implications for applicability of a generalized arterial transfer function.